Hope and athlete burnout: Stress and affect as mediators - Gustafsson, H.; Skoog, T.; Podlog, L.; Lundqvist, C.; Wagnsson, S. (Psychology of Sport and Exercise, 2013)
Objective: In this study we examined the relationship between trait hope and burnout in elite junior soccer players and whether stress and positive and negative affect mediated this relationship. Methods: Participants were 238 Swedish soccer players (166 males, 71 females; one did not indicate gender) aged 15-19 years who completed questionnaires measuring trait hope, perceived stress, positive and negative affect, and athlete burnout (i.e., emotional/physical exhaustion, a reduced sense of accomplishment, and sport devaluation). Results: Bivariate correlations were consistent with hope theory contentions indicating significant negative relationships between hope and all three burnout dimensions. The relationship between hope and emotional/physical exhaustion was fully mediated by stress and positive affect. For sport devaluation and reduced sense of accomplishment, stress and positive affect partially mediated the relationship with hope. In contrast, negative affect did not mediate the relationship between hope and any of the burnout dimensions. Conclusion: The results support earlier findings that hope is negatively related to athlete burnout. Support was also found for the hypothesis that high hope individuals would experience less stress and therefore less burnout. Promoting hope may be relevant in reducing the likelihood of this detrimental syndrome.